Simulation of Air Flow on Modified Generic Shape of an Automotive Side View Mirror - Nur Rashid, Mat Nuri @ Md Din; Ir. Dr. Shuhaimi, Mansor (2011)
In this paper, an aerodynamics effect of modified generic side view mirror geometry which has different upper lip and lower lip length is discussed. The numerical simulation is done by using Computational Fluid Dynamics (CFD) software which is FLUENT using k-epsilon standard turbulence model. The results obtained are discussed in term of pressure coefficient, Cp and velocity distribution at side mirror surface. Results obtained had been compared with other researchers work. With all these results, the effect of upper and lower lips length on air flow characteristic have been determined and optimization of side view mirror shape has been proposed.